Polaronic proton and diproton clustering in neutron-rich matter - Hiroyuki Tajima; Hajime Moriya; Wataru Horiuchi; Eiji Nakano; Kei Iida (Physics Letters B, 2024)
We show that the strong spin-triplet neutron-proton interaction causes polaronic protons to occur in neutron matter at subnuclear densities and nonzero temperatures. As the neutron density increases, proton spectra exhibit a smooth crossover from a bare impurity to a repulsive polaron branch; this branch coexists with an attractive polaron branch. With the neutron density increased further, the attractive polarons become stable with respect to deuteron formation. For two adjacent protons, we find that the polaron effects and the neutron-mediated attraction are sufficient to induce a bound diproton, which leads possibly to diproton formation in the neutron skin region of neutron-rich nuclei in laboratories as well as in neutron stars.